The Effects of Norms on Investor Reactions to Derivative Use - Koonce, Lisa; Miller, Jeffrey; Winchel, Jennifer (Contemporary Accounting Research, 2015)
Abstract Prior research indicates that a firm's use of derivatives to manage business risks is viewed favorably by investors. However, these studies do not consider a potentially key factor in this setting—namely, the typical behavior (or norms) regarding derivatives by other firms in the industry or the firm itself. In this paper, we report the results of multiple experiments that test whether norms are influential in affecting investors’ evaluations of firms’ derivatives choices. Our results show that the generally favorable reactions to derivative use actually reverse and become unfavorable when firms’ derivative decisions are inconsistent with industry or firm norms. Somewhat surprisingly, though, we find that industry and firm norms are not viewed similarly by investors. These results expand our understanding of how investors respond to firm's derivative use decisions and demonstrate the role of norms as factors that influence investors’ judgments in financial reporting settings. Our results have implications for firm managers making decisions about derivative use.